(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the history of the oil industry in the Ferghana Valley in 1917-1924. and shows the importance of this industry in the development of the economy and the growth of industry as a whole. The political, social processes, changes in all sectors of the economy initiated by the totalitarian Soviet government, which influenced the extraction of oil from oil wells, and the processes of its processing, were studied. The article is devoted to the history of the oil industry in the Ferghana Valley in 1917-1924. based on archival documents from the funds of the National State Archives of Uzbekistan, scientific research by foreign and domestic researchers and includes conclusions on the topic.